The Antigen Presenting Potential of CD21low B Cells - Reincke, Marlene E.; Payne, Kathryn J.; Harder, Ina; Strohmeier, Valentina; Voll, Reinhard E.; Warnatz, Klaus; Keller, Baerbel (Frontiers in Immunology, 2020)
Human CD21low B cells are expanded in autoimmune (AI) diseases and display a unique phenotype with high expression of co-stimulatory molecules, compatible with a potential role as antigen-presenting cells (APCs). Thus, we addressed the co-stimulatory capacity of naïve-like, IgM-memory, switched memory and CD27negIgDneg memory CD21low B cells in allogenic co-cultures with CD4 T cells. CD21low B cells of patients with AI disorders expressed high levels of CD86, CD80 and HLA-DR (memory B cells), but also PD-L1 ex vivo and efficiently co-stimulated CD4 T cells of healthy donors (HD), as measured by upregulation of CD25, CD69, Inducible Co-stimulator (ICOS), programmed cell death protein 1 (PD-1) and induction of cytokines. While the co-stimulatory capacity of the different CD21low B-cell populations was over all comparable to CD21pos counterparts of patients and HD, especially switched memory CD21low B cells lacked the increased capacity of CD21pos switched memory B-cells to induce high expression of ICOS, IL-2, IL-10 and IFN-. Acknowledging the limitation of the in vitro setting, CD21low B cells do not seem to preferentially support a specific Th effector response. In summary, our data implies that CD21low B cells of patients with AI diseases can become competent APCs and may, when enriched for autoreactive B-cell receptors (BCR), potentially contribute to AI reactions as cognate interaction partners of autoreactive T cells at sites of inflammation.